Isolation of Potential Amylase Producing Bacillus albus and Bacillus paramycoides Bacteria from Sugarcane Bagasse - Khan, Muhammad Saeed; Ullah, Saif; Khan, Faryal; Mehtab, Sundas; Ullah, Waheed (Asian Journal of Biological and Life Sciences, 2025)
Background: Enzymes are biological catalysts that play essential roles in metabolic pathways, digestion, energy production, and industrial applications. Amylase, an enzyme that catalyzes the hydrolysis of starch into simpler sugars, is widely used in food, fermentation, textile, and biofuel industries. Microbial amylases, particularly those from the Bacillus species, are preferred due to their high yield and efficiency. This study focuses on the isolation, screening, and optimization of amylase-producing bacteria from sugarcane bagasse soil samples. Materials and Methods: Soil samples were collected from sugarcane bagasse sites in Peshawar, Pakistan, and subjected to serial dilution and plating on nutrient agar. Isolates were screened for amylase activity using starch agar plates and iodine staining. The highest amylase-producing isolates were further tested for optimal production conditions, including pH and temperature. Morphological, biochemical, and molecular identification of bacterial isolates were performed, including 16S rRNA gene sequencing. Results: Among the 10 bacterial isolates, 8 exhibited amylase activity, with 4 isolates (G2, A1, S2, and M1) showing the highest hydrolysis zones. The optimal pH for amylase production was determined to be pH 10 for all isolates, with M1 producing the highest enzyme activity (0.211 IU/mL/min). Temperature optimization revealed that isolates varied in their thermal preference: G2 (45ºC), A1 (70ºC), S2 (40ºC), and M1 (70ºC), suggesting thermostability. Morphological and biochemical analyses confirmed that the isolates belonged to the Bacillus genus. Molecular identification and phylogenetic analysis revealed that A1 had 94.34% similarity with Bacillus paramycoides, while G2 showed 94.25% similarity with Bacillus albus. Conclusion: The findings suggest that these strains, particularly the thermotolerant isolates, hold significant industrial potential for enzyme production under alkaline and high-temperature conditions.
Keywords: Amylase; Bacillus albus; Bacillus paramycoides; Enzyme activity; Sugarcane bagasse